The Effect of Moringa Leaf Extract and Katuk Leaf Extract on Exclusive Breastfeeding with Increased Breast Milk Production in Postpartum Mothers - Heryani, Lusi; Munawaroh, Madinah; Sugesti, Retno (Universitas Prima Indonesia, 2025)
Low breast milk production is one of the primary challenges in achieving exclusive breastfeeding among postpartum mothers. This study aims to examine the effect of moringa leaf extract and katuk leaf extract on increasing breast milk production in postpartum mothers on the second day after delivery at Panimbang Public Health Center in 2025. The research employed a Study Case Literature Review (SCLR) method with a qualitative case study approach. Two postpartum mothers with low milk production were given interventions for seven days: one received moringa leaf extract and the other received katuk leaf extract, each at a dose of two capsules per day. Breast milk volume was measured on the 3rd, 5th, and 7th day using a measuring cup. The results showed that breast milk production increased from 50 cc to 120 cc in the respondent who consumed moringa extract (a difference of 70 cc), and to 140 cc in the respondent who consumed katuk extract (a difference of 90 cc). These findings indicate that both extracts effectively increase breast milk production, with katuk leaf extract yielding greater results. This study recommends the use of moringa and katuk leaves as natural alternatives to support the success of exclusive breastfeeding.